An Overview of Autophagy in Helicobacter pylori Infection and Related Gastric Cancer - Yang, Yihan; Shu, Xu; Xie, Chuan (Frontiers in Cellular and Infection Microbiology, 2022)
Helicobacter pylori (H. pylori) infection is considered a class I carcinogen in the pathogenesis of gastric cancer. In recent years, the interaction relationship between H. pylori infection and autophagy has attracted increasing attention. Most investigators believe that the pathogenesis of gastric cancer is closely related to the formation of an autophagosome-mediated downstream signaling pathway by H. pylori infection-induced cells. Autophagy is involved in H. pylori infection and affects the occurrence and development of gastric cancer. In this paper, the possible mechanism by which H. pylori infection affects autophagy and the progression of related gastric cancer signaling pathways are reviewed.